Routinised and compulsive‐like behaviours in individuals with Down syndrome. (1st June 2015) - Glenn, S.; Cunningham, C.; Nananidou, A.; Prasher, V.; Glenholmes, P.
Abstract Background Increased intensities of routinised and compulsive‐like behaviours are seen in those with intellectual disabilities and have sometimes been shown to be associated with worries. We used the Childhood Routines Inventory (CRI, Evans et al., 1997) with two samples of children and adults with Down syndrome: (1) to determine whether routinised and compulsive‐like behaviours were associated with mental health problems and (2) to determine the factor structure of the CRI. Method Parents or carers completed the CRI for (1) 125 adults with Down syndrome (aged 18–43 years) who had been assessed for mental health problems; worries and fears were also rated by parents/carers and (2) 206 individuals with Down syndrome (aged 4.5–43 years, with verbal mental ages of 2 years and above). Results (1) People with a psychiatric diagnosis had significantly more worries and fears than those without such a diagnosis, but there was no significant difference in CRI scores. Logistic regression indicated that the fear rating was the only significant predictor of a diagnosis. (2) Exploratory and confirmatory analyses showed a three‐factor model (Just right, Repetitive behaviour and Clothes sensitivity) to be the best solution. Those with psychiatric diagnoses had significantly higher ratings on the Repetitive behaviour factor. Conclusion Increased levels of routinised and compulsive‐like behaviours were shown by individuals with Down syndrome of all ages, were not associated with mental health problems, but were associated with worries and fears. Factor analysis found three factors, two of which (Just right and Repetitive behaviours), were similar to those identified in typically developing samples. This suggests that the behaviours have similar adaptive functions in individuals with developmental delays.